Two identical beakers are filled with acid solutions, the ratio of the volume of acid to the volume of water being p:1 in one beaker and q:1 in the other beaker. If the entire contents of the two beakers are mixed together, the ratio of the volume of acid to the volume of water is:
Solution
This looks nasty, but here we go.
If the ratio of acid to water is p:1, then if the beaker contains x cc's of liquid total, which means (p+1p)×x cc’s are acid and (p+11)×x cc’s are water. The same goes for q:1. (q+1q)×x is acid and (q+11)×x is water.
The total acid is:
(p+1p+q+1q)x=(p+1)(q+1)(p(q+1)+q(p+1))x=(p+1)(q+1)(2pq+p+q)x
The total water is:
(p+11+q+11)x=(p+1)(q+1)(p+1+q+1)x=(p+1)(q+1)(p+q+2)x
So acid/water = (p+1)(q+1)(2pq+p+q)x÷(p+1)(q+1)(p+q+2)x=p+q+22pq+p+q, which is e.
It’s getting started that’s hard.